THE PRODUCTION ANALYSISOF FLOATING CAGES BUSINESS IN KELURAHAN HARANGGAOL SUB DISTRICT OF HARANGGAOL HORISON SIMALUNGUN REGENCY OF NORTH SUMATRA PROVINCE - Sipayung, Ropita Adelina; ', Zulkarnaini; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on 26 January to 9 February 2016 on the Village of Lake Toba Haranggaol Haranggaol Horison Simalungun District of North Sumatra province . The method used in this study by survey method . Based on research result that the Business floating cages in the Village Haranggaol annually require seed is 164.352.000 Tilapia fish tail, fish seed Mas ie 242.000 a year tail, catfish fish seed is 90.000 tails year, and Patin of 60.000 head a year. The amount of feed for tilapia fish each year is 46.224.000 kg, feed the fish Mas is 96.600 kg a year, fish feed catfish is 8.100 kg a year, and Patin fish feed is 36.000 kg a year. Production of tilapia in floating net cages every year is 28.761,6 tons a year, the production of carp that is 64.4 tons a year, the production of catfish 9 tons a year, and the catfish production of 24 tons a year. Keywords :Analysis, Production, Floating Net Cage, Lake Toba